Mechanisms underlying the development of type 1 diabetes in ART-treated people living with HIV: an enigmatic puzzle - Zaongo, Silvere D.; Zongo, Abel W.; Chen, Yaokai (Frontiers in Immunology, 2024)
The immunopathogenesis of HIV infection remains poorly understood. Despite the widespread use of effective modern antiretroviral therapy (ART), people living with HIV (PLWH) are known to develop several comorbidities, including type 1 diabetes (T1DM). However, the etiology and critical mechanisms accounting for the onset of T1DM in the preceding context remain unknown. This article proposes to address this topic in order to provide further understanding and future research directions.